Reduced coronary flow velocity reserve in women with previous pre‐eclampsia: link to increased cardiovascular disease risk. (10th May 2020) - Clemmensen, T. S.; Christensen, M.; Løgstrup, B. B.; Kronborg, C. J. S.; Knudsen, U. B.
ABSTRACT: Objectives: To evaluate differences in coronary microvascular function approximately 12 years after delivery between women who had had early‐ (EO‐PE) or late‐ (LO‐PE) onset pre‐eclampsia and those who had had a normotensive pregnancy, and to assess the relationship between microvascular function and myocardial deformation at follow‐up in these women. Methods: This was a case–control study of 88 women who had delivered at the Department of Gynecology and Obstetrics, Randers Regional Hospital, Randers, Denmark, between 1998 and 2008. Coronary flow velocity reserve (CFVR) was assessed by Doppler echocardiography approximately 12 years after delivery. Women were grouped according to whether the pregnancy had been complicated by EO‐PE ( n  = 29) or LO‐PE ( n  = 20), or had been normotensive (controls) ( n  = 39). Study groups were matched for maternal age and time since delivery. CFVR at follow‐up was compared between the study groups. Regression analysis was used to assess the association between gestational age at onset of PE and CFVR. The association between left ventricular global longitudinal strain (LV‐GLS) and CFVR at follow‐up was also evaluated. Results: Resting coronary flow velocity assessed 12 years after delivery was comparable between the study groups ( P  = 0.55), whereas peak hyperemic flow velocity was significantly lower in the EO‐PE group than in the LO‐PE group ( P  < 0.01) and controls ( P  < 0.0001). As such, mean CFVR at follow‐up was significantly lower in the EO‐PE group than in the LO‐PE group ( P  < 0.01) and controls ( P  < 0.0001). CFVR was < 2.5 in 48% of women in the EO‐PE group, 25% of those in the LO‐PE group and 8% of controls ( P  < 0.01). There was a significant positive association between gestational age at diagnosis of PE and CFVR at 12‐year follow‐up (β1 = 1.8 (95% CI, 0.8–2.9); P  < 0.01). This relationship remained significant after adjustment for cardiovascular risk factors, namely mean arterial blood pressure, glycated hemoglobin level, body mass index, low‐density lipoprotein cholesterol level and smoking status ( P  < 0.05). There was a significant association between LV‐GLS and CFVR in women who had had PE (β1 = –1.5 (95% CI, –2.2 to –0.9); R 2  = 0.33, P  < 0.0001). Conclusions: Low gestational age at onset of PE, both as a continuous variable and when categorized as early onset, was associated with decreased CFVR 12 years after delivery. Nearly 50% of women who had had EO‐PE had CFVR < 2.5 at follow‐up. Reduced CFVR in women who had had PE was associated with subclinical myocardial dysfunction in terms of reduced LV‐GLS. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.